Program Effectiveness, Governance, and Household Welfare: A Path Analysis of Indonesia’s Free Nutritious Meal Program in East Jakarta - Indria, Audrey Belinda (Journal of Social Work and Science Education, 2026)
This study analyzes the influence of Free Nutritious Meal Program (MBG) effectiveness and program governance on household economic welfare in East Jakarta, Indonesia. Using a quantitative survey design, data were collected from 402 MBG beneficiary households selected through purposive sampling. Path analysis was employed to examine direct and indirect relationships among program governance, program effectiveness, and household economic welfare. Results indicate that program governance has a positive and significant effect on program effectiveness (β = 0.323, p < 0.001), and program effectiveness in turn has a positive and significant effect on household economic welfare (direct effect not fully reported in current manuscript). However, the model explains only 10.5% of the variance in program effectiveness and 6.7% of the variance in household economic welfare, suggesting that unmeasured factors such as household income, employment status, food prices, and social support networks play substantial roles in determining welfare outcomes. These findings confirm that good governance (transparency, accountability, and efficient distribution) enhances program effectiveness, and effective programs contribute to household welfare by reducing food expenditure burdens. The study contributes to the literature on social protection governance by demonstrating that program success depends not only on resource allocation but also on governance quality. Limitations include cross-sectional design (precluding causal inference), low explanatory power, and geographic restriction to East Jakarta. Future research should incorporate additional welfare determinants and employ longitudinal designs.